2016
DOI: 10.1007/s12072-016-9763-0
|View full text |Cite
|
Sign up to set email alerts
|

Functionally aberrant dendritic cell subsets and expression of DC-SIGN differentiate acute from chronic HBV infection

Abstract: The initial events of immune activation might be responsible for modulating immune response. These novel observations would pave the way for the development of antiviral strategies for chronic HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, despite efficient internalization, HBV does not trigger IFN‐α, IL‐6, and TNF‐α secretion by pDCs . HBV not only does not activate pDCs, but also actively inhibit their function . Cytokine production of pDCs differs significantly between CHB patients and healthy individuals.…”
Section: Pdcs and Hbvmentioning
confidence: 97%
“…However, despite efficient internalization, HBV does not trigger IFN‐α, IL‐6, and TNF‐α secretion by pDCs . HBV not only does not activate pDCs, but also actively inhibit their function . Cytokine production of pDCs differs significantly between CHB patients and healthy individuals.…”
Section: Pdcs and Hbvmentioning
confidence: 97%
“…Similar data indicate reduced expression of dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin and reduced secretion of IFNa and IFNk. (29,30) However, in vitro human DC2s secreted IFNk in response to HCV exposure, and this in turn provoked the secretion of IFNa from pDCs, suggesting an innate immune activation cascade. (31) Although there is little information about DCs within hepatitis virus-infected human liver, we know the proportion of DC1s and DC2s are changed.…”
Section: Dendritic Cells In Viral Hepatitismentioning
confidence: 99%
“…Other studies reported that the maturation of pDCs was impaired after stimulation with TLR agonists in patients with chronic HBV infection. In addition, pDCs not only produced decreased IFN‐alpha (IFN‐α), TNF‐α, and IFN‐lambda1 (IFN‐λ1) but also expressed perturbed C‐type lectin receptors which play a crucial role in orchestrating with DCs to respond to pathogens 37–39 . Dysfunction of DCs caused by HBV is a potential mechanism for chronic HBV infection and restoring DC functions may offer a new option for curing persistent HBV infection (Figure 2).…”
Section: Introductionmentioning
confidence: 99%